PARAPENAEOPSIS INDICA, SP. NOV. (DECAPODA, PENAEIDAE) FROM THE INDIAN WATERS - Muthu, M S (Indian Journal of Fisheries, 2011)
Parapenaeopsis indica, a species new to science, is described based on material collected from Kakinada along the east coast of India. The features that distinguish P. indica from the closely related species are discussed. In August 1968, some specimens of what appeared to be young Parapenaeopsis sculptilis were collected from the Kakinada fish market. Subsequently similar specimens were collected from the Kakinada canal, Kakinada Bay and from the nearshore waters at Godavary Point. On closer examination they were found to differ from all known species of Parapenaeopsis and hence they are described here in detail as a species new to science.